Evaluation of Muhammadiyah University of Riau Science Education Study Program Students' Environmental Literacy in Peat and Mangrove (PeMA) - Purwanto, Hadi; Sholihat, Neng; Novalia, Melly; Solehatunisa; Apriani, Ade (Biosfer: Jurnal Tadris Biologi, 2026)
Environmental literacy plays an important role in developing students’ awareness and responsibility toward environmental sustainability, particularly in response to global ecological challenges. However, students’ environmental literacy levels remain relatively moderate, indicating the need for more contextual and meaningful learning approaches. This study examined the environmental literacy of science education students in relation to peatland and mangrove ecosystems. A quantitative approach with a one-group pretest–posttest design was employed. The participants were science education students at Muhammadiyah University of Riau enrolled in an environmental education course. Data were collected using an environmental literacy test adapted from the MSELS instrument, covering four domains: knowledge, cognitive skills, attitudes, and behavior. Data were analyzed using descriptive and inferential statistics. The results showed that students’ environmental literacy was categorized as moderate, with an overall score of 139. These findings suggest that peatland- and mangrove-based learning supports environmental awareness, although more comprehensive context-based strategies are still needed. Evaluasi Literasi Lingkungan Mahasiswa Program Studi Pendidikan IPA Universitas Muhammadiyah Riau pada Ekosistem Gambut dan Mangrove (GAMA) ABSTRAK: Literasi lingkungan memegang peran penting dalam membentuk kesadaran dan tanggung jawab mahasiswa terhadap keberlanjutan lingkungan, terutama di tengah tantangan ekologis global. Namun, tingkat literasi lingkungan mahasiswa masih tergolong sedang, sehingga diperlukan pendekatan pembelajaran yang lebih kontekstual dan bermakna. Penelitian ini bertujuan mengkaji literasi lingkungan mahasiswa pendidikan IPA dalam konteks ekosistem lahan gambut dan mangrove. Penelitian menggunakan pendekatan kuantitatif dengan desain one-group pretest–posttest. Partisipan penelitian adalah mahasiswa Pendidikan IPA Universitas Muhammadiyah Riau yang menempuh mata kuliah pendidikan lingkungan. Data dikumpulkan menggunakan tes literasi lingkungan yang diadaptasi dari instrumen MSELS, yang mencakup empat domain, yaitu pengetahuan, keterampilan kognitif, sikap, dan perilaku. Data dianalisis menggunakan statistik deskriptif dan inferensial. Hasil penelitian menunjukkan bahwa literasi lingkungan mahasiswa berada pada kategori sedang dengan skor keseluruhan 139. Temuan ini menunjukkan bahwa pembelajaran berbasis lahan gambut dan mangrove mendukung peningkatan kesadaran lingkungan, meskipun masih diperlukan strategi pembelajaran kontekstual yang lebih komprehensif.